Associations Between Trunk Muscle/Fat Composition, Narrowing Lumbar Disc Space, and Low Back Pain in Middle-Aged Farmers: A Cross-Sectional Study - Baek, Sora; Park, Hee-won; Kim, Gowun (Annals of rehabilitation medicine, 2022)
Objective To investigate the association of trunk fat and muscle composition, lumbar disc space narrowing, and low back pain in middle-aged farmers.Methods Fat and muscle areas were identified using standard Hounsfield unit ranges for adipose tissue and skeletal muscle with computed tomography images at the mid-L4 vertebral level. Trunk fat mass, muscle mass, and fat/muscle mass ratio were calculated. Low back pain was assessed using the Oswestry Disability Index (ODI). The L4/5-disc space and low back pain were also assessed.Results Male had a higher total trunk, back, psoas, and abdominal muscle mass, and visceral fat; female had a higher subcutaneous fat mass and fat/muscle ratio. Pearson correlation coefficients with ODI for waist circumference, total fat mass, visceral fat mass, and fat/muscle ratio were all significant in female; only the fat/muscle ratio was significant in male. Pearson correlation coefficients with L4/5-disc space narrowing grades for visceral fat mass, total, back, and psoas muscle mass, and fat/muscle ratio, were all significant in female; total and back muscle mass, and fat/muscle ratio in male.Conclusion There were significant relationships between: fat indicators with low back pain; trunk muscle mass with lumbar disc degeneration; and fat/muscle ratio with both lumbar disc degeneration and low back pain. The fat/muscle ratio may be a useful index for low back pain.